Strengthening effect of particle gradation on the mechanical properties of sand powder 3D printed rock analog - Zhe Zhang; Lishuai Jiang; Atsushi Sainoki; Xiaohan Peng; Chunang Li; Qingjia Niu; Xinzhe Wang; Mingwei Gang (Journal of Materials Research and Technology)
Sand powder 3D printing (SP-3DP) technology has garnered significant attention for its potential in fabricating rock analog, offering a cost-effective and versatile solution for various geological and engineering applications. However, the mechanical properties of SP-3DP specimens, particularly their strength and elastic modulus, often lag behind those of natural rocks. To address this discrepancy, a method for improving the mechanical properties of SP-3DP rock-like specimens through particle gradation is proposed. The effects of various particle sizes and gradations on the mechanical properties of these specimens were investigated through a series of mechanical tests, acoustic emission analysis, and scanning electron microscopy. The results indicate that: (1) the mechanical properties of SP-3DP specimens are significantly enhanced by optimal particle gradation; (2) the reinforcement mechanism of particle gradation for the mechanical properties of SP-3DP specimens is elucidated; and (3) the effectiveness and applicability of the optimized specimens are verified. This study significantly enhances the strength and elastic modulus of SP-3DP rock-like specimens, broadening the application scope of SP-3D printing technology in rock mechanics and materials science, and providing a foundation for more accurate simulation of rock behavior under complex geological conditions.